(untitled) (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
This article contains information about the life of Mahmudhaja Behbudi, the father of Turkestan jadids, who greatly contributed to the development of jadidism in Turkestan, his travels and movement in opening schools of jadidism, as well as books written in order to make new method schools and people educated, and the libraries he opened.